Answer:
![y=-\frac{x}{6} -1](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7Bx%7D%7B6%7D%20-1)
Step-by-step explanation:
Hi there!
We are given the following equation:
x+6y=-6
And we want to convert it into slope-intercept form
Slope-intercept form is known as y=mx+b, where m is the slope and b is the y intercept
The equation is currently in standard form, which is ax+by=c, where a, b, and c are integer coefficients
Notice how in standard form, both the terms that contain x and y are on one side, but in slope-intercept form, y is by itself on one side
So essentially, in order to convert from standard form to slope-intercept form, we need to solve for y
Here is our equation again:
x+6y=-6
Start by subtracting x from both sides
x+6y=-6
-x -x
_______________
6y=-x-6
Now divide both sides by 6
![y=-\frac{x}{6} -\frac{6}{6}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7Bx%7D%7B6%7D%20-%5Cfrac%7B6%7D%7B6%7D)
We can simplify the fractions to become:
![y=-\frac{x}{6} -1](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7Bx%7D%7B6%7D%20-1)
Hope this helps!
See more on converting from standard to slope-intercept form here: brainly.com/question/26579052